ACT victims of crime referral project: final report - Hannah Andrevski
This report presents the findings of a project funded by Victim Support ACT and ACT Policing to examine the experiences of victims referred by police to support services and the operation of the referral process in the ACT. Since the completion of the report in 2009, Victim Support ACT and ACT Policing have used it to facilitate better access to support services for people affected by crime. Following the establishment of the Victims Advisory Board in 2011, the Victims of Crime Commissioner sought the support of the Board to progress matters that had been raised in the report. The Commissioner was of the view that the Board, having a function to develop and maintain protocols and procedures for the treatment of victims by agencies involved in the administration of justice, was well placed to assist Victim Support ACT and ACT Policing to progress these issues. To assist the Board to perform this function, the report is now being published to allow public access to the information